6 - Genre et commerce équitable au Cameroun * - Tchouassi, Gerald (Africa Development, 2007)
The article seeks, through an analysis of literature on gender, to illustrate how basic principles of fair trade can permit the reading of the position of women in international exchange or their access to world trade. Using the hypothesis that women are the main creators of fair trade enterprises in Cameroon, the paper employs a socio-economic approach to analyse relevant data on Cameroon. In conclusion, the paper highlights certain basic principles to be respected in order to secure gender equality in fair trade. The distribution channel permits the set- ting up of a ‘Fair Price’ for goods produced that take into account ethics and the real costs of production, rather than simply coming under the influence of multi- nationals and big distributors present in the various sectors of production.